An evidence-based review of the relationship between leadership and accountability - Melo, Pedro Novo (2020)
Accountability is an essential element in all societies and to the organizations that inhabit this world. Corporate scandals have been linked to failures in accountability and business leaders are now more than ever challenged to be accountable. Leadership can also be understood as a response to transparency and accountability issues that are an important concern in the area of public administration. In substance, leadership and accountability are both attributional phenomena. We conduct an evidence-based review using an integrative synthesis of published peer-reviewed literature on leadership and accountability. Our search in Web of Science databases identified 37 articles on this topic of several research areas. Our review of these articles addresses the following 5 questions: (1) What kind of studies have been developed on the topic? (2) What is the possible relationship between leadership and accountability? (3) What is the impact of studies identified in the literature? (4) What is the incidence of studies in the area of Business and Economics? (5) Which direction should subsequent studies take? To answer these questions, we use an evidence-based review with bibliometric methods of citation analysis, co-citation analysis, co-author analysis, and co-word analysis. We conclude that despite evidence linking the adoption of a relationship between leadership and accountability, adoption is very low, particularly in the field of business and economics, and therefore, evidence on this topic is sparse. This study intends to contribute to a more complete reflection and understanding of literature review, impact and relevance of accountability in organizational leadership. We offer potential explanations for this paradox and suggest avenues for future research.